The wear of Stone Mastic Asphalt due to slow speed high stress simulated laboratory trafficking. (1st May 2016) - Woodward, David; Millar, Philip; Lantieri, Claudio; Sangiorgi, Cesare; Vignali, Valeria
Graphical abstract: Highlights: An investigation into the wear SMA road surfacing material has been proposed. The Wear Test using the Road Test Machine has used. The relationships between SMA design and surface properties have been investigated. Abstract: This paper summarizes a laboratory investigation into the wear of Stone Mastic Asphalt road surfacing material. Review of harmonized European test methods found no specific Wear Test and this is an important knowledge gap relating to laboratory prediction. The UK Wear Test using the Road Test Machine was applied to assess Stone Mastic Asphalt test specimens. This uses full size pneumatic tires to wear asphalt test specimens, under slow speed high stress conditions. This found 14 mm and 10 mm SMA to behave in similar ways. Relationships between variables for newly compacted test specimens quickly change with the onset of simulated trafficking. This raises issues with laboratory investigations that do not involve some aspect of tire/test specimen wear at their interface. Contact area is a better property to measure than macrotexture. Poor relationships between contact area and pendulum tester suggest that either something additional at the contact interface has to be measured or there are limitations with the pendulum tester. More research is required to better understand wear at the tire–asphalt interface and the prediction/measurement/monitoring/modeling of properties such as skid resistance, rolling resistance and noise generation.